Robust classification of dental tissues using LIBS data based on data reconstruction and distance prior strategy - Shuting Lin; Xingwei Yi; Lei Yan; Shanshan Liang; Fusong Yuan (Analytica Chimica Acta, 2026)

Food-derived extracellular vesicles modulate ferroptosis: Implications for functional food development and healthy aging - Lin Zhang; Wangying Qiu; Mingrun Lu; Shuting Lan; Zuokai Lv; Haiyan Zhang; Yue Pang; Xingcan Zhang; Wenjing Xu; Haitao Wang; Jiahui Liu; Jiahui Ma; et al. (Food Research International, 2026)

A fish-skin-inspired wearable scale-ionogel composite for impact protection and motion sensing - Tianyu Xu; Zimu Li; Lin Mei; Hanshen Huang; Jie Tian; Zijian Mei; Shuting Liu; Xiaoming Liu; Xinglong Gong; Tianzhi Luo (Chemical Engineering Journal, 2026)

Enabling fast Li+ transport in cellulose nanocrystals polymer electrolytes via grafting flexible acrylates for stable solid-state lithium metal batteries - Xinyan Lv; Shuting Liu; Lin Peng; Sheng Liu; Zhenkun Liu; Zuyun Chen; Xiaoyuan Yu (Carbohydrate Polymers, 2026)

Enhanced volatile fatty acids production from anaerobic co-fermentation of waste activated sludge and food waste via electrochemical pretreatment: Performance of carbon source utilization, safety and economic analysis - Qingshan Lin; Lihong Wang; Kejie He; Li Li; Shuting Liang; Yeqing Li; Zichong Zhu; Gang Guo (Journal of Water Process Engineering, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Dynamics of kinetic energy in rill headcut erosion and sediment yield characteristics within granitic red soil regions - Shuyu Luo; Jianyu Wang; Zhe Lin; Jiangxing Wei; Wencong Liang; Hongyu Liu; Fang Wang; Guiwan Yan; Shuting Liu; Xiaoqian Duan; Yusong Deng (CATENA, 2026)

A machine learning-based model for soil iron oxides estimation using fused hyperspectral and multispectral data - Yongshi Tan; Zhenxi Wei; Yan Xiao; Yulin Huang; Zongxin Li; Shuting Yang; Lin Zou; Lanhui Yang; Yusong Deng (Journal of Soils and Sediments, 2026)

Optimisation study of a geometric-VOF model based on elementary symmetric polynomial and adaptive time-step Crank-Nicolson method - Ziming Xu; Yanjun Liu; Zaibin Lin; Shuting Huang; Hao Chen; Gang Xue (Ocean Engineering, 2026)

The role of cue transparency in task switching: an SDM-PSI meta-analysis in healthy adults - Xiaoyu Zheng; Yidan Qiu; Shuting Lin; Wenzhao Deng; Zhizhong Jiang; Bin A. Wang; Ruiwang Huang (Brain Imaging and Behavior, 2026)

An extra-large panicle gene ELP1 from wild rice Oryza officinalis increases grain number and grain yield - Jiachen Ma; Mei Li; Yanan Lin; Jinjin Lian; Yizhengnan Zhu; Jing Yang; Wenfan Hu; Luyi Zhang; Shuting Li; Weilin Zhang (Theoretical and Applied Genetics, 2026)

Influence of initial headcut height on rill headcut erosion mechanisms via runoff hydrodynamics modulation in granite residual soil - Jianyu Wang; Zhe Lin; Jiangxing Wei; Wencong Liang; Hongyu Liu; Fang Wang; Guiwan Yan; Shuting Liu; Xiaoqian Duan; Yusong Deng (Journal of Hydrology, 2025)

Electrospun polyvinyl alcohol/chitosan-ZIF-8@cyanidin cation-gallic acid multifunctional nanofilm for real-time visual monitoring of beef freshness - Qian Liang; Maonan Xu; Yalan Peng; Junwen Huang; Minjian Liao; Dongsong Lin; Yongkai Chen; Wuyi Zhou; Wenxu Zheng; Xianming Dong; Shuting Zhang (Chemical Engineering Journal, 2025)

Microtopography promoting Benggang erosion: Formation and stability of niche on collapsing wall - Wencong Liang; Ling He; Zhe Lin; Shuting Liu; Jianyu Wang; Shuyu Luo; Yusong Deng (Geomorphology, 2025)

Polystyrene Microplastics Induce Insulin Resistance and Glucose Metabolism Disorders in Grass Carp (Ctenopharyngodon idellus) via the Gut Microbiome–Metabolism Axis - Fubin Zhang; Shuting Huang; Xueting Chen; Zhendong Qin; Li Lin (Fishes, 2025)
Polystyrene microplastic (PS-MP) particles disrupt aquatic biological systems due to their persistence and high bioaccumulation potential, causing structural damage and inflammatory responses. PS-MPs also act as metabolic disruptors, affecting glucose metabolism and insulin signaling, although the mechanisms underlying these effects remain unclear. In this study, grass carp were exposed to 100 μg/L and 400 μg/L of polystyrene MPs for 30 days. Histopathological analysis showed the shortening of intestinal villi, vacuolization, and inflammatory infiltration. Antioxidant enzyme activities (SOD and CAT) were reduced, while the presence of tissue damage markers (GPT and GOT) was elevated, suggesting a biphasic oxidative stress response. Transcriptomic analysis revealed downregulation of genes related to metabolism and insulin signaling, especially at 400 μg/L. Gene set enrichment analysis (GSEA) highlighted pathways related to insulin resistance and type 2 diabetes, indicating the disruption of glucose metabolism. Microbiome analysis showed reduced diversity, expansion of Proteobacteria (opportunistic pathogens), and a decrease in beneficial bacteria like Bacillus. These shifts correlated with changes in the expression of key insulin signaling genes, emphasizing the role of host–microbiota interactions in metabolic imbalances. This study revealed that PS-MPs disrupt glucose metabolism and insulin signaling in grass carp through a combination of histological damage, oxidative stress, and microbiota dysbiosis.

Integrated metabolomics and transcriptomics reveal the nutritional profiles and molecular mechanisms in colored cauliflowers - Xiaoguang Sheng; Mengfei Song; Jiansheng Wang; Huifang Yu; Yusen Shen; Shuting Qiao; Fan Lin; Sifan Du; Honghui Gu (Food Bioscience, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

Greenery strategies for reducing pedestrian particulate exposure along an open-flanked urban arterial road - Zhanyong Wang; Yanying Rao; Xinyuan Lin; Shuting Chen; Xisheng Hu (Urban Climate, 2025)

Optimal scheduling of industrial park integrated energy systems considering dynamics of multiple fluid networks - Yihui Mao; Xiaojie Lin; Shuting Zhang; Jiale Wang; Wei Zhong; Baoqin Liu; Guangyue Xia (Journal of Cleaner Production, 2025)

Buprofezin causes early developmental toxicity of zebrafish (Danio rerio) embryos: morphological, physiological and biochemical responses - Shuting Qiang; Yufeng Che; Mingyang Lu; Yuan Tian; Lin Gao; Jingwen Chen; Tingzhang Hu (Aquatic Toxicology, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

New insights into the effects of PFOS exposure on rat lung development: morphological, functional, and single-cell sequencing analysis - Jiali Mo; Jingye Zuo; Lin Yu; Huishan Zhang; Shuting Weng; Leping Ye (Archives of Toxicology, 2025)

Quantifying permafrost thawing and its impact on lake storage dynamics in the Qinghai-Tibet Plateau - Shuting Ji; Pan Wu; Lin Chen; Yingjie Yang; Xuehui Pi; Jeffrey M. McKenzie; Xiuyu Liang (Journal of Hydrology, 2025)

Distribution characteristics and influencing factors of benthic diatoms on several typical beaches along the southern coast of China - Min Chen; Jiayu Li; Guobiao Huang; Yanting Lin; Shuting Zeng; Ya Xu; Xuan Liu; Feng Cai; Hongshuai Qi (Marine Environmental Research, 2025)

Enhanced antioxidant potential of In vitro gastrointestinal digestion products derived from abalone myofibrillar protein-glucose conjugates based on structural changes - Gengxin Hao; Yanwen Ma; A.YiJiang Akemujiang; Yanping Bai; Peng Ye; Xujian Qiu; Shuting Lin (Food Bioscience, 2025)

Modification of microporous bionanocomposite films with visible light-activated photocatalytic antimicrobial TNT-CuO nanoparticles for active fruit packaging - Huan Zhang; Shuting Huang; Yali Zhao; Hong Sabrina Tian; Mengshi Lin; Yunfei Xie; Zhilong Yu (Food Research International, 2025)

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

Effects of soil microorganisms on aggregate stability during vegetation recovery in degraded granitic red soil areas - Shuting Liu; Zhe Lin; Xiaoqian Duan; Yusong Deng (Applied Soil Ecology, 2024)

Soil application of graphitic carbon nitride nanosheets alleviate cadmium toxicity by altering subcellular distribution, chemical forms of cadmium and improving nitrogen availability in soybean (Glycine max L.) - Kai Xu; Lifan Zheng; Kaifei Chu; Chenghua Xing; Jiajing Shu; Keming Fang; Shuting Ma; Yong Fang; Jianfang Yan; Miaozhen Cai; Xi-Lin Wu (Journal of Environmental Management, 2024)

Antimicrobial effect of plasma-activated water combined with tartaric acid against Staphylococcus aureus and its application on fresh-cut asparagus lettuce - Wei Wu; Jing Zhang; Tangjun Li; Zhenyang Hu; Shuting Huang; Mengshi Lin; Yunfei Xie; Zhilong Yu (Food Bioscience, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

The effects of different drying methods on the flavor profile of wheat germ using E-nose and GC-IMS - Yang Zhong; Gexing Zhang; Fangqin Zhang; Shuting Lin; Mei Wang; Yue Sun; Jin Liang; Xueling Li (Journal of Cereal Science, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Measuring and modeling the effects of green barriers on the spatial distribution of fine particulate matter at roadside - Xin Chen; Jie Wu; Wenbin Yang; Zhanyong Wang; Shuting Chen; Xisheng Hu; Kaifa Lu; Zhongmou Fan; Mei Lin; Pu Chen (Urban Climate, 2023)

Soil calcium constrains nitrogen mineralization and nitrification rates in subtropical karst regions - Shuting Yang; Lin Yang; Dongni Wen; Lijun Liu; Kang Ni; Jianhua Cao; Tongbin Zhu; Christoph Müller (Soil Biology and Biochemistry, 2023)

Isolation and characterization of an endophytic fungi from Zingiber officinale Rosc. and its activity to promote the growth of tissue culture ginger plantlets in bottles - Shuting Zhang; Yinghong Pei; Jiao Wang; Xiaolong Lin; Zizhong Tang; Lijun Zhou; Tao Chen; Shiling Feng; Chunbang Ding; Yanger Chen; Zhongwei Zhang; Shu Yuan; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

Quantitative study on steam system thermal inertia based on a dynamic hydraulic analytical model - Wei Zhong; Shuting Zhang; Xiaojie Lin; Jiale Wang; Yi Zhou (Journal of Cleaner Production, 2023)

Fabrication of covalent organic frameworks modified nanofibrous membrane for efficiently enriching and detecting the trace polychlorinated biphenyls in water - Yuancai Lv; Jiachen Ma; Zhendong Yu; Shuting Liu; Guifang Yang; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Yongqian Shi; Minghua Liu (Water Research, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

Free radical mechanism of toxic organic compound formations from o-chlorophenol - Xiaoyun Liu; Guorui Liu; Shuting Liu; Linjun Qin; Bingcheng Lin; Mingxuan Wang; Lili Yang; Minghui Zheng (Journal of Hazardous Materials, 2023)

Editorial: Advances in estuarine and coastal nitrogen cycle - Jing Wei; Xiyang Dong; Shuting Liu; Xianbiao Lin (Frontiers in Marine Science, 2023)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Molecular characterization of miRNA genes and their expression in Dimocarpus longan Lour - Yuling Lin; Yan Chen; Youjing Zeng; Shuting Zhang; Zihao Zhang; YuKun Chen; Jiawei Gong; Zhongxiong Lai (Planta, 2021)

Characteristics and health risk assessments of heavy metals in PM2.5 in Taiyuan and Yuci college town, China - Xiaofeng Liu; Zhilei Wang; Huiling Bai; Shuting Zhang; Ling Mu; Lin Peng (Air Quality, Atmosphere & Health, 2020)

The function of advanced treatment process in a drinking water treatment plant with organic matter-polluted source water - Huirong Lin; Shuting Zhang; Shenghua Zhang; Wenfang Lin; Xin Yu (Environmental Science and Pollution Research, 2017)

PLFA profiles of drinking water biofilters with different acetate and glucose loadings - Xin Yu; Xu Shi; Bo Wei; Lin Ye; Shuting Zhang (Ecotoxicology, 2009)